Agentivité, devenir-chasseur et affects - Patrick Deshayes (Ateliers d'Anthropologie)
This article studies the specific affects of Huni Kuin hunters based on a combination of two concepts: that of “agency” and that of “becoming”, borrowed from Deleuze and Guattari. For the Huni Kuin, there is continuity between hunting and certain diseases. The same agents control disease and game. This article shows how this continuity is conceived and constructed and what effect it has on a hunter’s everyday life.